The regulation of ζ-globin expression - King, A (2019)
Expression of the embryonic α-like globin gene, ζ-globin, is limited to the early stages of primitive erythropoiesis. Under normal circumstances it is completely silenced in definitive erythroid cells, despite lying adjacent to a “super-enhancer” composed of five separate enhancer elements. Here, the chromatin environment has been characterized within the mouse ζ-globin cluster between primitive erythroblasts when ζ-globin expression is maximal, and definitive erythroblasts, when ζ-globin is silenced. In primitive erythropoiesis, the α globin locus is contained within an identical ~80kb erythroid-specific self-interacting chromosomal domain as found in definitive erythroid cells, delimited by the same CTCF boundary elements and with the same five enhancer elements. Changes in chromatin accessibility across the locus between primitive and definitive erythropoiesis are limited to the ζ-globin promoter which is markedly accessible in primitive erythropoiesis, and inaccessible in definitive erythroblasts. NG-Capture C shows that ζ-globin remains within the same self-interacting domain as in definitive erythroid cells although the contact between the enhancers and the ζ-globin promoter is significantly reduced. Recently, a novel immortalised human erythroid cell line, the HUDEP-2 line, has been described. Here, it is shown that this serves as an appropriate model for studying ζ-globin silencing. Using the HUDEP-2 cell line, primary human erythroid cells, primitive and definitive erythroid cells in mice and previously published data sets, it is shown that histone deacetylation and chromatin remodelling are responsible for ζ-globin silencing: the PRC2 complex, DNA methylation and H3K9me2/me3 do not play a role. BCL11A and LRF together are responsible for silencing of the fetal stage β-like γ-globin gene and its murine orthologue. Using mouse models where these transcription factors have been perturbed, it is apparent that both play a crucial role in the silencing of ζ-globin with their removal leading to increased ζ-globin expression and changes in chromatin accessibility over the ζ-globin gene. Knockout of BCL11A and LRF in HUDEP-2 cells has similar effects, with knockout of both together leading to an increase in expression of ζ-globin to ~15% of the total α-like globins. Analysis of published CUT&RUN; and ChIP-seq data sets show that both BCL11A and LRF bind directly to the ζ-globin promoter. Knockout of LRF and BCL11A together in definitive erythroid cells does not lead to restoration of the level of ζ-globin expression to that seen in primitive erythropoiesis. This means that other transcription factors must be responsible. To facilitate screening of activating and repressive transcription factors and complexes, a new mouse model, where a yellow fluorescent protein variant replaces exon 3 of the endogenous ζ-globin gene, has been generated and characterised. This can also be used for screening drugs capable of de-repressing ζ-globin. Because exon 3 of the ζ-globin gene is removed in this mouse model, this knocks out ζ-globin when present in homozygosity. Live births of ζ-null mice are significantly decreased, but viable phenotypically normal mice can be born, indicating that ζ-globin is advantageous, but not essential, for normal development.